Happiness among low-income adults in Kuala Lumpur, Malaysia is linked to other social factors, not income level - Burhan, Nik Ahmad Sufian; Rosnon, Mohd Roslan; Sabri, Mohamad Fazli; Hamsan, Hanina H.; Kinainah, Mohd Nor Hafizuddin; Bustami, Mohammad Reevany (Ulster Institute for Social Research, 2024)
Research frequently indicated that improving impoverished people’s income would improve their happiness. However, does this association hold true for low-income households in Malaysia’s urban areas? This study conducted a cross-sectional survey of 356 individuals aged 18 to 65 from low-income households in Kuala Lumpur, Malaysia, to assess the impact of income and other socioeconomic factors on happiness, using a regression model adapted from the World Happiness Report (WHR). The homogeneous convenience sampling approach was employed to collect the data, which were subsequently analyzed using regression analysis, incorporating the robust M-estimators. The results of regression analyses showed that happiness was not significantly associated with income, gender, having a spouse, education level, being not unemployed, and number of dependents. Strong evidence (p < .01) of a U-shaped curve was discovered for the relationship between happiness and age through robust regressions. Among all predictors, freedom to make life choices produced the largest effect on happiness (β = 0.48 to 0.55). Health status (β = 0.14 to 0.16), social support (β = 0.12), generosity (β = 0.10 to 0.15), and perceptions of corruption (β = −0.11 to −0.12) were also significant in most regressions. The potential directions of social policy goals are discussed based on the observation that income is not a significant predictor. This includes promoting good governance and preventing corruption, as well as providing societies with more options and improving citizens’ autonomy, all of which will lead to greater freedom and a more positive attitude towards the government. Finally, developing strategies to build social interactions among community members is critical because this will foster a more supportive and generous society, which contributes to happiness.